2002
DOI: 10.1212/wnl.58.8.1282
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced muscle “burning,” fatigue, and hyper-CKemia: mtDNA T10010C mutation in tRNA Gly

Abstract: A 42-year-old woman presented with myopathy and without a family history of neuromuscular disorder. Muscle biopsy showed ragged red fibers and reduced activities of mitochondrial respiratory chain enzyme complexes I, III, and IV. Analysis of mitochondrial DNA revealed a heteroplasmic T10010C mutation in the transfer RNA glycine gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Mitochondrial DNA depletion, caused by nuclear TK2 gene mutations Saada et al, Asp are shown. The mutation (arrows) in our patient is shown in red, the mutations in the previously published patients are shown in orange and pink [Katsumata et al, 1994;Shtilbans et al, 1999] [Chinnery et al, 1997;Hadjigeorgiou et al, 1999;Dey et al, 2000;Shoffner, 2001;Sternberg et al, 2001;Vives-Bauza et al, 2001;Nishigaki et al, 2002;Horvá th et al, 2003;McFarland et al, 2004]. This list shows that although some common mtDNA mutations, such as the tRNA Lys A8344G, can occasionally present as isolated mitochondrial myopathy, this is usually not the cause of isolated mitochondrial myopathy.…”
Section: Discussionmentioning
confidence: 64%
“…Mitochondrial DNA depletion, caused by nuclear TK2 gene mutations Saada et al, Asp are shown. The mutation (arrows) in our patient is shown in red, the mutations in the previously published patients are shown in orange and pink [Katsumata et al, 1994;Shtilbans et al, 1999] [Chinnery et al, 1997;Hadjigeorgiou et al, 1999;Dey et al, 2000;Shoffner, 2001;Sternberg et al, 2001;Vives-Bauza et al, 2001;Nishigaki et al, 2002;Horvá th et al, 2003;McFarland et al, 2004]. This list shows that although some common mtDNA mutations, such as the tRNA Lys A8344G, can occasionally present as isolated mitochondrial myopathy, this is usually not the cause of isolated mitochondrial myopathy.…”
Section: Discussionmentioning
confidence: 64%
“…Total DNA from peripheral blood leukocytes, cultured skin fibroblasts, and autopsy tissues was extracted by standard procedures. A series of PCR-amplified fragments of the DNA encompassing first the 22 tRNA genes in mtDNA and then the entire mtDNA was sequenced directly in an ABI Prism 310 Genetic Analyzer using Big Dye Terminator Cycle Sequencing Reaction Kits (Perkin-Elmer Applied Biosystems, Foster City, California, USA) using standard procedures (12). Restriction fragment length polymorphism (RFLP) analyses were performed on DNA from peripheral blood leukocytes, cultured skin fibroblasts, and autopsy tissues.…”
mentioning
confidence: 99%
“…Individual white colonies were cultured independently in TB medium with ampicillin. Approximately 100 cloned plasmids were purified using the High Pure Plasmid Isolation Kit (Roche Diagnostics Corp., Indianapolis, Indiana, USA) and were sequenced directly in an ABI Prism 3700 Genetic Analyzer (Perkin-Elmer Applied Biosystems) following standard procedures (12).…”
mentioning
confidence: 99%
“…Here we describe a novel heteroplasmic mutation at position 4308 in the mtDNA MT-TI gene in a patient with CPEO and hyperCKemia, the last one uncommonly observed in mitochondrial disorders related to mtDNA mutations [11,12]. We believe that this mutation is pathogenetic for the following reasons:…”
Section: Discussionmentioning
confidence: 87%